2008
DOI: 10.1007/s12325-008-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent primary open-angle glaucoma and cataract: Preliminary analysis of treatment by cataract surgery and the iStent trabecular micro-bypass stent

Abstract: In this interim analysis of subjects with glaucoma and cataracts, this novel stent implantation in subjects undergoing cataract surgery represents a new surgical approach to provide clinically significant decreases in IOP and drug burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 18 publications
9
58
1
1
Order By: Relevance
“…10 This was also the experience of Le et al 12 who recommended early tapering of steroids. Steroid response may partly explain the delay in the peak IOP lowering effect following iStent insertion, usually at 3 months post-insertion, 7,11 which was also what we found in our study. There was no long-term adverse event in the 3-year follow-up period in our study group, suggesting that the procedure is a safe and effective longterm method of lowering IOP.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…10 This was also the experience of Le et al 12 who recommended early tapering of steroids. Steroid response may partly explain the delay in the peak IOP lowering effect following iStent insertion, usually at 3 months post-insertion, 7,11 which was also what we found in our study. There was no long-term adverse event in the 3-year follow-up period in our study group, suggesting that the procedure is a safe and effective longterm method of lowering IOP.…”
Section: Discussionsupporting
confidence: 86%
“…4,10 Among other adverse events reported in studies are stent malposition or occlusion early in the post-operative period, affecting 4% to 18% of cases but usually resolved with observation alone or secondary procedures such as Nd:YAG laser, argon laser gonioplasty, recombinant tissue plasminogen activator, stent repositioning, or stent replacement. 10,11 Steroid response was found in 2 of 53 eyes 4 weeks post-operatively in a case series where IOP was controlled after cessation of steroids. 10 This was also the experience of Le et al 12 who recommended early tapering of steroids.…”
Section: Discussionmentioning
confidence: 98%
“…10 By comparison, phacotrabeculectomy reduces IOP mean by 8.2mmHg. Conjunctiva is reflected, and a scleral flap is cut as in a trabeculectomy.…”
Section: Ab-interno Micro Stent To Bypass Trabecular Resistancementioning
confidence: 98%
“…The ocular hypotensive efficacy seen with the stent in this study was found to be consistent with the trabecular bypass mechanism of action and results described in literature. (Fea, 2010;Spiegel et al, 2008Spiegel et al, & 2009 Compared with cataract surgery alone, implantation of the iStent concomitant with cataract extraction significantly increases trabecular outflow facility, reduces IOP and the number of medications. (Fernandez-Barrientos et al, 2010) A study in cultured human anterior segments has shown that a single stent created the largest change in IOP, resulting in a mean of 12.4 ± 4.2 mm Hg, corresponding to an 84% increase in facility of outflow.…”
Section: Scientific Evidence So Farmentioning
confidence: 99%